Pelatihan Prosedur Digitalisasi Pelayanan Kependudukan Pada Kantor Kecamatan Jatisampurna - Santhuso, Agus; Kurnia C, Kurnia C; H , Heny; Affar, M; Tiara, Tiara; Khomala Syari, Whindy (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Customer Service is the leading front in an institution in providing services to the community. The success and satisfaction provided to the user community is one of the superior values ??of this institution. The State Civil Service Agency (BKN) is a state institution that operates in the field of state personnel management which provides administrative services to civil servants. With the training and counseling attended by 80 administrative staff regarding public speaking / communication in general, creativity and professional training in providing assistance to civil servants who need data, it is hoped that this will help make it easier for employees to provide customer service in the Directorate section. Procurement and Rankings in the State Civil Service Agency.